The coverage of vaccination in the Malay newspapers: an exploratory study - Wan Mohd Ghazali, Wan Norshira; Mohamed, Shafizan; Mohd Nasir, Nur Shakira; Yusoh, Mohd Helmi (Global Network of Communication Scholars, 2020)
The return of vaccine-preventable diseases such as polio, diphtheria, measles, mumps and the likes indicates the increasing popularity and effectiveness of the anti-vaccine movement in inseminating its sentiments. Effective news media coverage on vaccination that highlights the urgency and importance of vaccination to the general public is needed to counter the vaccine misconceptions that are currently abundant especially in the social media. In the attempt to investigate whether the news media is playing its role in effectively covering vaccination issues, this study explores vaccine coverage in two Malay newspaper dailies, Berita Harian and Harian Metro. Quantitative framing analysis was conducted on a total of 131 vaccine- related news collected for nine months from January 2019 to September 2019. All the news was studied to ascertain the extent of coverage, types of frames and sources used in reporting vaccination issues. The findings found some differences in the numbers and ways the two dailies covered about vaccination. Despite the variation, the study found that there is still a lack of emphasis on vaccination given by the Malay newspapers. Vaccination is mostly seen as news to be reported and not an issue to be highlighted and emphasized. Thus in relation to current health realities, it is pertinent that the Malay newspapers paly a more significant role in promoting the importance vaccination.